2019
DOI: 10.1080/02656736.2019.1668065
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control for MR-HIFU-mediated, uniform hyperthermia

Abstract: Purpose: In local hyperthermia, precise temperature control throughout the entire target region is key for swift, safe, and effective treatment. In this article, we present a model predictive control (MPC) algorithm providing voxel-level temperature control in magnetic resonance-guided high intensity focused ultrasound (MR-HIFU) and assess the improvement in performance it provides over the current state of the art. Materials and methods: The influence of model detail on the prediction quality and runtime of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…That assembly enabled them to penetrate more deeply towards the center of tumour spheroids which is an important breakthrough considering the intrinsic difficulty to penetrate in the core of a solid tumour.High-intensity focused ultrasounds (HIFU) is a novel therapeutic strategy based on acoustic energy for the thermal ablation of deep-seated tumours. While still under development, proof of concept studies demonstrated that this HIFU-based moderate HT allows higher temperature uniformity within the tumour[100]. In mice skeletal muscle, pulsed-HIFU were found to enhance the delivery of…”
mentioning
confidence: 99%
“…That assembly enabled them to penetrate more deeply towards the center of tumour spheroids which is an important breakthrough considering the intrinsic difficulty to penetrate in the core of a solid tumour.High-intensity focused ultrasounds (HIFU) is a novel therapeutic strategy based on acoustic energy for the thermal ablation of deep-seated tumours. While still under development, proof of concept studies demonstrated that this HIFU-based moderate HT allows higher temperature uniformity within the tumour[100]. In mice skeletal muscle, pulsed-HIFU were found to enhance the delivery of…”
mentioning
confidence: 99%
“…22,23 Numerical solutions of (6) and (9) were obtained by applying a regular finite-difference method, as per the procedure mentioned in a previous study. 22 The ultrasound field and temperature elevation were coupled through (4). The model configuration is consistent with that the experiments, which is illustrated in Fig.1.…”
Section: A Theoretical Models and Simulationmentioning
confidence: 57%
“…For a long time, heat transfer in biological tissues is usually predicted with the well-known Pennes equation proposed in 1948 [3,4], which describes heat conduction in terms of the Fourier series expansion. However, when used to describe temperature distribution in hyperthermia such as HIFU, microwave, and radiofrequency ablation, validity of Pennes equation faces challenge [5].…”
Section: Introductionmentioning
confidence: 99%
“…For focused ultrasound (FUS), the ellipsoidal focal spot typically has dimensions of a few mm in diameter, up to $1 cm in length, which decreases with increasing frequency and aperture. US technology enables excellent spatial and dynamic control of the power and temperature distribution [39] due to its relatively short wavelength (a few millimeters) and allows deep penetration in soft tissues, provided an US window is present. These properties enable conformal tumor heating for both ablation and hyperthermia by mechanically or electronically scanning a highly focused US beam through the target region [40][41][42].…”
Section: Ultrasoundmentioning
confidence: 99%
“…This provides better lesion control as it can compensate real-time for local differences in ultrasound absorption or heat loss due to perfusion. Recently, a model predictive control algorithm in combination with MR temperature mapping was introduced for a voxel-based heating strategy that allows compensation for local heat losses e.g., due to perfusion, with a high spatial resolution [39]. MR thermometry finds now routine use in all MR-HIFU applications [388,389].…”
Section: Thermometrymentioning
confidence: 99%